2016
DOI: 10.1007/s00705-016-3202-3
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and genome analysis of novel bacteriophages infecting the opportunistic human pathogens Klebsiella oxytoca and K. pneumoniae

Abstract: Klebsiella is a genus of well-known opportunistic human pathogens that are associated with diabetes mellitus and chronic pulmonary obstruction; however, this pathogen is often resistant to multiple drugs. To control this pathogen, two Klebsiella-infecting phages, K. oxytoca phage PKO111 and K. pneumoniae phage PKP126, were isolated from a sewage sample. Analysis of their host range revealed that they infect K. pneumoniae and K. oxytoca, suggesting host specificity for members of the genus Klebsiella. Stability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Interestingly, in the temperature range from −20 and 70 • C, it was observed that ZCKP8 was relatively thermally stable. ZCKP8 maximal activity was detected at 50 • C, with a moderate decrease of 2 log 10 PFU/mL at 70 • C. K. pneumoniae phages, including wKp-lyy15, phage Z, PKP126, vB_Klp_1, vB_Klp_3, vB_Klp_4, vB_Klp_5, and vB_Klp_6, were previously mentioned to be active at 70 • C [29][30][31].…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Interestingly, in the temperature range from −20 and 70 • C, it was observed that ZCKP8 was relatively thermally stable. ZCKP8 maximal activity was detected at 50 • C, with a moderate decrease of 2 log 10 PFU/mL at 70 • C. K. pneumoniae phages, including wKp-lyy15, phage Z, PKP126, vB_Klp_1, vB_Klp_3, vB_Klp_4, vB_Klp_5, and vB_Klp_6, were previously mentioned to be active at 70 • C [29][30][31].…”
Section: Discussionmentioning
confidence: 84%
“…ZCKP8 maximal activity was detected at 50 °C, with a moderate decrease of 2 log 10 PFU/mL at 70 °C. K. pneumoniae phages, including wKp-lyy15, phage Z, PKP126, vB_Klp_1, vB_Klp_3, vB_Klp_4, vB_Klp_5, and vB_Klp_6, were previously mentioned to be active at 70 °C [ 29 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of those which are reported as targeting K . oxytoca , most belong to the Myoviridae family, with genomes ranging in size from 168 to 174 Kb [ 30 , 31 , 43 ]. KOX1, the unique K .…”
Section: Discussionmentioning
confidence: 99%
“…pneumoniae were able to lyse strains of K . oxytoca [ 30 , 31 , 43 ], KOX1 was specific for K . oxytoca bacteria, and did not readily lyse the K .…”
Section: Discussionmentioning
confidence: 99%
“…Stability of the phages to temperature and pH was assessed by phage titration after incubation in SM buffer at different temperature or pH values (Park et al, 2017). Briefly, 1.5 mL tubes containing the same amount of the purified phages…”
Section: Thermal and Ph Stabilitymentioning
confidence: 99%